Karakterisasi Morfologi dan Biokimiawi Berbagai Kultivar dan Aksesi Jeruk Pamelo (Citrus maxima (burm.) merr.) di Kabupaten Magetan - Istiqomah, Intan Lailatul; Suratman, Suratman; Solichatun, Solichatun (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study examines the morphological characteristics, sugar content, and antioxidant activity of various cultivars and accessions of Pomelo Orange in Magetan Regency. Samples were taken using a purposive sampling method. Morphological characters were observed based on IPGRI characterization, while antioxidant activity analysis was carried out using a UV-Vis spectrophotometer. Morphological character data were analyzed descriptively and antioxidant activity was analyzed by One Way Anova method and followed by DMRT (Duncan's Multiple Range Test) test. The results showed that (1) the highest inhibition percentage was found in the Srinyonya cultivar in Takeran, which was 76.15%; (2) Overall, Pomelo Orange cultivars have antioxidant activity with IC50 values ranging from 5.78–27.17 ppm, indicating strong antioxidant activity; (3) The sugar content in various cultivars ranges from 8–10 °Brix, with the highest levels found in the Javanese cultivar in Sukomoro, which was 10.7 °Brix.